Tafsir Sosial Media di Indonesia - Fadhli Lukman (Nun : Jurnal Studi Alquran dan Tafsir di Nusantara, 2016)
The history of contemporary exegesis sees the integration between the Quran and exegesis and social media. A statistic shows the low reading rates of Indonesians while the reading activity is dominated by social media. It leads to an assumption that the social media exegesis is the one people read nowadays. This paper takes this phenomena into account within two main concerns: (1) how is the different ways people use their social media account for the Quran related content, and (2) how is the notion of the social media exegesis as a contemporary exegesis? The article ends to the conclusion that there are at least three different shapes of the social media exegesis: textual, contextual, and tafsīr `ilmī. It marks the rise of semantic function of the Quran among the people and the shift of authority of exegesis. There are three causes for it: the platform of social media, the availability of the Quran translation, and the paradigm of al-rujū` ilā al-qur`ān wa al-sunnah.